The role of licenses in public utility services provision – 19th century experiences - Adamczyk, Elżbieta (Studia Historiae Oeconomicae, 2015)
The subject of this article is a part of a broader debate related to the participation of the private sector in the execution of public services. It concerns those services which are provided to recipients in the conditions of a natural monopoly, based on a license (so with the privilege of exclusivity) awarded to private companies for executing the state’s tasks. This paper aims at outlining the reasons behind the implementation of similar solutions and the problems related to entrusting the private party with satisfying public needs – problems which revealed a conflict of interest between the parties of the licensing contract.